'Content to be sad' or 'runaway apprentice'? The psychological contract and career agency of young scientists in the entrepreneurial university. (May 2015) - Lam, Alice; de Campos, André
This article examines employee agency in psychological contracts by exploring how young scientists proactively shape their careers in response to unmet expectations induced by academic entrepreneurialism. It uses the lens of social exchange to examine their relationships with the professors engaged in two types of activities: collaborative research characterized by diffuse/reciprocal exchange, and commercial ventures, by restricted/negotiated exchange. These two categories show how career agency varies in orientation, form and behavioural outcome depending on the relational context within which their psychological contracts evolve. Those involved in collaborative research experienced a relational psychological contract and responded to unfulfilled career promises by 'extended investment' in their current jobs. They use 'proxy agency' by enlisting the support of their professors. However, some become 'trapped' in perennial temporary employment and are 'content to be sad'. By contrast, those involved in research commercialization experienced a transactional contract and assert 'personal agency' by crafting their own entrepreneurial careers. They are 'runaways' who seek autonomy. The evidence is based on interviews with 24 doctoral/postdoctoral researchers and 16 professors from three leading UK universities. The article extends psychological contract theory by incorporating career agency and sheds new light on changing academic careers.